Artista-professor: processos criativos e ensino-aprendizagem em arte - Oliveira, Gabriela Clemente de (2018)
I assume that the artist-teacher is a subject who has knowledge from experience in art. Far beyond being a subject who has academic training in a bachelor's degree or degree in art, the artist-teacher is one who knows the process of creation, complex in nature, and who has the opportunity to access different knowledge constructed through the fair relationship between reason and intuition. The artist-teacher, endowed with this sensitive knowledge, can provide a particular environment in the teaching-learning relationship in which the principles of experience can also be experienced by their students. I used the theories of Dewey, Cecília Almeida Salles, Fayga Ostrower, Jorge Larrosa, among others, with the intention of creating a relationship between creative processes, experience and teaching-learning in art. I believe that its presence in education can consolidate true research practices in art.